Subjectivity[]Culture[]Communications[]Intermedia: A Meditation on the "impure interactions" of Performance and the "in-between" Space of Intimacy in a Wired World - Barton, Bruce (Theatre Research in Canada / Recherches théâtrales au Canada, 2008)
This "meditation" pursues four objectives. The first is to provide an introduction to a variety of psychological interpretations of the concept of intimacy in terms of its motivations, characteristics, and functions within the larger understanding of the construction, maintenance, and expansion of the "self" in relationship and interaction. The second objective is to attempt to locate these psychological observations on intimacy within broader socio-anthropological frameworks, in order to consider if and how they are manifest in cultural and ideological developments. The third objective is to overlay these initial findings with multiple theories of communications and media influence on individuals and communities, as they relate to the reformation of and potential for intimacy in contemporary mediatized societies. The pursuit here is of a composite "logic" of resonance, interconnection, and generalized causality within these overlapping evolutionary spheres (psychology, sociology, communications). The fourth objective is to elucidate (as opposed to "define") the elusive concept of intermedia as it is understood, analyzed, and enacted by contemporary practitioners and theorists, with a particular emphasis on the role of intimacy in terms of intention, design, and experience. Finally, the emerging theoretical insights generated are tentatively applied to a performance by the intermedial, site-specific performance troupe Bluemouth Inc. Presents. In the process of these inquiries, I hope to establish intermedia—and, specifically, intermedial intimacy—as the recognizable (though not necessarily inevitable) offspring of the previously explored personal, cultural, and ideological developments. Résumé Cette « méditation » poursuit quatre objectifs. Le premier : présenter diverses interprétations du concept d’intimité tel qu’il est entendu dans le domaine de la psychologie (motivations, caractéristiques et fonctions) et les placer dans le cadre plus large de la construction, de l’entretien et de l’expansion du « soi » dans le contexte d’une relation et d’une interaction. Le second objectif : inscrire ces observations sur l’intimité dans un cadre socio-anthropologique plus vaste pour voir si on les retrouve dans des développements culturels et idéologiques. Le troisième objectif : superposer à ces premières constatations quelques théories de la communication ayant trait à l’influence des médias sur l’individu et la société en rapport avec la réforme de l’intimité et son potentiel dans des sociétés contemporaines médiatisées. Cet objectif est celui d’une « logique » composite de la résonnance, de l’interconnexion et de la causalité généralisée au sein même des sphères évolutionnaires qui se chevauchent (psychologie, sociologie, communication). Le quatrième objectif est de clarifier (plutôt que « définir ») le concept insaisissable d’intermédia tel que l’entendent, l’analysent et le mettent en œuvre des praticiens et théoriciens contemporains. Une importance toute particulière est accordée au rôle de l’intimité en ce qui a trait à l’intention, à la conception et à l’expérience. Et enfin, l’auteur tentera de mettre en pratique les théories en émergence en se servant de l’exemple d’une représentation intermédia localisée de la compagnie Bluemouth Inc. Au fil de son enquête, l’auteur souhaite montrer que l’intermédia – et plus précisément, l’intimité intermédia – est le produit reconnaissable (mais pas nécessairement inévitable) d’événements personnels, culturels et idéologiques explorés auparavant.